Normative parameters and anthropometric variability of lumbar muscle stiffness using ultrasound shear-wave elastography. (February 2019) - Koppenhaver, Shane L.; Scutella, Dominique; Sorrell, Brooke A.; Yahalom, Joshua; Fernández-de-las-Peñas, Cesar; Childs, John D.; Shaffer, Scott W.; Shinohara, Minoru
Abstract: Background: Quantifying stiffness of the lumbar spine musculature using shear-wave elastography (SWE) maybe beneficial in the diagnosis and treatment of non-specific low back pain (LBP). The primary purpose of this study was to establish normative parameter and variance estimates of lumbar spine muscle stiffness at rest and during submaximal contraction levels using SWE in healthy individuals. A second aim was to determine the relationship between lumbar spine muscle stiffness and a variety of demographic, anthropometric, and medical history variables. Methods: This cross-sectional study included stiffness measurements of the lumbar musculature in 120 asymptomatic individuals using ultrasound SWE. The lumbar erector spinae muscle was measured during rest only and lumbar multifidus muscle was measured during rest and during submaximal contraction using a prone contralateral arm lift. Statistical comparisons of shear modulus were made between sex (male vs. female) and muscle condition (erector spinae rest, lumbar multifidus rest, lumbar multifidus contracted) using 2 × 3 repeated measures analysis of variance (ANOVA). Univariate associations between shear modulus and age, sex, BMI, activity level, and history of back pain were assessed using correlation analysis. Findings: Shear modulus at rest was approximately 4 kPa for the erector spinae muscles and approximately 6 kPa for the lumbar multifidus muscles. Shear modulus substantially increased during contraction, and varied by sex, BMI, and self-reported activity level, with men and more active individuals generally having stiffer muscles. Interpretation: Variability in shear modulus of the lumbar musculature may be mediated through a combination of muscle size and contractile state, which is consistent with our findings of higher stiffness in the more postural lumbar multifidi muscles, during contraction, and in larger and more active individuals. These findings should inform and be accounted for in future comparative clinical studies. Highlights: Shear modulus at rest is approximately 4 kPa for the erector spinae muscles. Shear modulus at rest is approximately 6 kPa for the lumbar multifidus muscles. Shear modulus of the lumbar multifidus substantially increases during contraction. Shear modulus also varies by sex, BMI, and self-reported activity level. Men and larger and more active individuals generally have stiffer lumbar muscles.